2022
DOI: 10.3389/fimmu.2022.1007579
|View full text |Cite
|
Sign up to set email alerts
|

The development and improvement of immunodeficient mice and humanized immune system mouse models

Abstract: Animal models play an indispensable role in the study of human diseases. However, animal models of different diseases do not fully mimic the complex internal environment of humans. Immunodeficient mice are deficient in certain genes and do not express these or show reduced expression in some of their cells, facilitating the establishment of humanized mice and simulation of the human environment in vivo. Here, we summarize the developments in immunodeficient mice, from the initial nude mice lacking T lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 112 publications
1
41
0
1
Order By: Relevance
“…Nude mice are the earliest immunodeficient mouse strains. Mice with allele mutations in the foxn1 gene on chromosome 11 exhibit a hairless phenotype, congenital athymia, and the inability to produce T lymphocytes such that their range of immune responses involving lymphocytes is restricted [8]. However, in nude mice, T lymphocytes leak to a certain extent during growth [9], and B lymphocytes and NK cells remain active and mediate a series of immune responses.…”
Section: Construction and Optimization Of Pdx Modelsmentioning
confidence: 99%
“…Nude mice are the earliest immunodeficient mouse strains. Mice with allele mutations in the foxn1 gene on chromosome 11 exhibit a hairless phenotype, congenital athymia, and the inability to produce T lymphocytes such that their range of immune responses involving lymphocytes is restricted [8]. However, in nude mice, T lymphocytes leak to a certain extent during growth [9], and B lymphocytes and NK cells remain active and mediate a series of immune responses.…”
Section: Construction and Optimization Of Pdx Modelsmentioning
confidence: 99%
“…Finally, xenotransplantation studies typically employ compromised temperatures and other conditions to enable human cells to be propagated in zebrafish [ 120 ]. For some studies, mouse models may be superior, although they too have limitations [ 142 ].…”
Section: Limitations and Future Prospectsmentioning
confidence: 99%
“…Regeneration studies can also consider other immune populations, including for example, adaptive immune cells, dendritic cells, mast cells and M1 versus M2 macrophages [ 19 , 106 ]. Future cancer studies can further study the role of angiogenesis [ 122 ] and better mimic the human tumor microenvironment [ 129 ], including creating humanized models as achieved in mice [ 142 ]. Finally, so-called cancer ‘avatars’ have application in patient-specific ‘precision’ cancer therapy pipelines, with the potential to directly predict patient outcomes and thus influence individual patient care [ 143 , 144 ].…”
Section: Limitations and Future Prospectsmentioning
confidence: 99%
“…However, subspecies of R3327 only metastasized to the lymph nodes and lungs and did not form bone metastasis, limiting its usefulness in research of bone metastatic disease [ 30 ]. Dogs were also found to spontaneously acquire prostate cancer, and studies found that prostate cancer in dogs were not only rare, but lacked the membrane androgen receptor (AR) [ 31 32 ]. As a result, prostate hyperplasia seen in dogs always occur independently of ARs, which limits its application to human prostate disease research [ 33 34 ].…”
Section: Bone Metastatic Animal Modelsmentioning
confidence: 99%
“…To conduct more in-depth studies on the efficacy of immunotherapy in bone metastatic prostate cancer, animal models utilizing human prostate cancer cells that mimic the metastatic cascade and form osteoblastic bone lesions while maintaining immune capacity are needed. Researches regarding immunodeficient mice with humanized immune systems are under development and may help to alleviate the hardships of studying immunotherapy with animal models [ 32 ].…”
Section: Future Directionmentioning
confidence: 99%